Evaluation of the structural changes of the hand joints and the rates of rheumatoid arthritis progression according to ultrasound data - Rita Aleksandrovna Osipyants; D E Karateev; E Yu Panasyuk; G V Lukina; A V Smirnov; S I Glukhova; E N Aleksandrova; A V Volkov; E L Nasonov (Научно-практическая ревматология)
Objective: to define the significance of ultrasonography (USG) in the diagnosis of early destructive changes in the hand joints and the rates of rheumatoid arthritis (RA) progression in patients at different ages of disease onset. Subjects and methods. 100 patients with a valid RA diagnosis (American College of Rheumatology (ACR) 1987 criteria were examined. They were divided into 2 groups: 1) 11 patients with an early RA history of less than 2 years (ERA); 2) 35 patients with a RA history of over 2 years (LRA). Hand USG (Voluson-i GE; a 4-13-MHz linear probe; gray scale mode) was carried out at baseline and after 6-month follow-up. A sonographic index (US-Er-10) based on the bilateral evaluation of 5 articular areas, such as wrinkles, second-to-third metacarpophalangeal (MCP) and second-to-third proximal interphalangeal (PIP) joints, was proposed to evaluate the progression of destruction. According to US-Er-10 changes, the rates of development of the destructive process were arbitrarily separated into three categories: 1) slow progression rate; 2) moderate progression rate; 3) a rapidly progressive course. The X-ray parameters of structural progression were estimated at 12-month follow-up, by employing the Sharp method modified by van der Heide (SHS). Results. The USG versus X-ray detection rate of erosions was significantly higher in both ERA and LRA (p < 0.05). The ERA patients who had fallen ill after 55 years of age were found to have more significant baseline and final destructive changes according to a total SHS score (p < 0.05) and US-Er-10 index (p < 0.005) than those with RA onset at a younger age. In the ERA patients in whom US-Er-10 increased by three points or more at 6-month follow-up, the rates of X-ray progression at 12 months were significantly higher than those with less pronounced negative changes in this index (Δ total SHS score of 13.5 [3-23] and 0 [0-0], respectively; p < 0.05). The LRA group displayed no statistically relationships between the USG rate of erosion progression and the time course of X-ray changes and laboratory evidence. Conclusion. Hand USG reveals early erosive joint changes significantly more frequently than X-ray study and the high progression rate of destruction according to USG and the disease with onset after 55 years of age are associated with its severer course and poor prognosis in patients with ERA.